An LCA methodolody for assessing the environmental impacts of building components before and after refurbishment. (10th December 2021) - Obrecht, Tajda Potrč; Jordan, Sabina; Legat, Andraž; Ruschi Mendes Saade, Marcella; Passer, Alexander
Abstract: Refurbishment is one of the most important measures for reducing the environmental impacts of the construction sector in the near future. According to the life cycle assessment (LCA) methodology for buildings, the environmental impacts of refurbishment measures should be assessed within the whole life cycle of the building and reflected in separate modules. However, in practice, refurbishment is often treated as the beginning of a new building life cycle. This leads to difficulties in correctly assessing the environmental impacts for the components that are reused or recycled after the refurbishment. The division of a building's life cycle into two separate life cycles indicates that the environmental impacts must be divided between the life cycle before and the life cycle after the refurbishment for a correct assessment of the environmental impacts and a calculation of the residual value. We propose a newly developed methodology for calculating the environmental impacts and the residual value of refurbishment measures that also involves a division between life cycles. The new methodology is a combination of already exiting methodologies that are innovatively combined and consists of four sequential steps. In the first step, the input, output and reuse flows between the life cycles before and after the refurbishment are defined. In the second step, the environmental impacts are assessed using the chosen allocation approach (i.e., the cut-off, cut-off with module D, avoided-burden, 50:50 and the product environmental footprint (PEF)). In the third step, a maintenance scenario is implemented according to the selected reference-service-life (RSL) database. In the fourth step, the residual value is estimated. The methodology was tested on selected building components. A sensitivity analysis for different allocation approaches and RSL databases was performed to show how the choice of these parameters can influence the results. The differences between the selected allocation approaches emerge if materials with recycled content are used or if the materials are being recycled or reused at the end of their life cycle. The developed methodology reliably estimates the environmental impacts as well as the residual value of the life cycle before and after the refurbishment. We expect that this research will stimulate practitioners to avoid the negligence of previous environmental flows, bringing scientific consistency to future assessments of refurbishment measures. Highlights: New methodology for calculating the impact of refurbishment, including different allocation approaches and RSL databases. Residual-value calculation with different allocation approaches and RSL databases. Graphical representation of separate allocation approaches, including calculation formulas. Differences between the allocation approaches appear in case of recycling and reuse of the materials.